Classification of Fruit Flies In South Kalimantan Based on Morphology and Molecular Characters - Pramudi, Muhammad Indar; Puspitarini, Retno Dyah; Rahardjo, Bambang Tri (Journal of Tropical Life Science, 2013)
The result of identification from assemblies trapped by methyl eugenol and collection of fruit affected fruit flies at all location, there are seven specieses of fruitfly in all locations. Based on morphological identification, which analyzed UPGMA by using the CLAD 97 program, shows that the seventh species remain one group that consists of 5 sub groups. On the other hand, according to RAPD result, which analyzed UPGMA based on 20 DNA band characters, shows that the seventh species divided into two groups. The first group consists of B. umbrosa Fabricius, B. occipitalisis Bezzi, B. latifrons Hendell sub groups. The second group consists of Bactrocera carambolae Drew and Hancock, B. papayae Drew and Hancock, and B. albistrigata de Meijere, B. cucurbitae Coquillet sub groups. Sequencing result shows that homology of seventh fruitfly species, is 83 base pairs/bp (C), 101 bp (T), 265 bp (G), 420 bp (A), 432 bp (T), 600 bp (A) (appendixes 7). The length base pair for B. occipitalis, B. cucurbitae, B. albistrigata, B. carambolae, B. papayae, B. latifrons row is 615, 898, 570, 969, and 615 bp. An analysis result of morphology feature and RAPD method show distinction in group division and sub group, but the identification morphological and DNA of the seventh species fruitfly which is found are the similar.Keywords: Fruitfly, UPGMA, Morphoogy, RAPD, DNA